Outcomes of dogs undergoing immediate or delayed surgical treatment for gastrointestinal foreign body obstruction: A retrospective study by the Society of Veterinary Soft Tissue Surgery. Issue 1 (26th September 2020) - Maxwell, Elizabeth A.; Dugat, Danielle R.; Waltenburg, Michelle; Upchurch, David; Soto‐Elias, Pedro; Duffy, Daniel J.; Spector, Daniel; Petrovsky, Brian; Payton, Mark
Abstract: Objective: To evaluate gastrointestinal injury and outcomes between dogs treated with immediate surgical intervention vs those treated with delayed surgical intervention for gastrointestinal foreign body obstruction (GIFBO). Study design: Retrospective cohort study. Sample population: Client‐owned dogs (n = 855) from five referral hospitals. Methods: Medical records of dogs in which GIFBO had been diagnosed between 2007 and 2017 were reviewed for preoperative management, timing of surgery, intraoperative findings, postoperative management, outcome, and survival. Surgical intervention was classified as immediate when it occurred within 6 hours of presentation and delayed when it occurred >6 hours after presentation. Results: Outcomes did not differ between dogs treated immediately (n = 584) or over 6 hours after presentation (n = 210). Intestinal necrosis and perforations were more common when surgery was delayed ( P = .008; P = .019) but became nonsignificant after controlling for preoperative differences. Risk factors for necrosis and perforations included duration of clinical signs, increased lactate, linear foreign material, and timing of surgery. Enterectomies ( P = .004) as well as the duration of surgery ( P = .004) and anesthesia ( P = .001) were increased when surgery was delayed. Immediate surgery was associated with earlier return to feeding ( P = .004) and discharge from the hospital ( P  < .001); (5%) dogs in each group (n = 33 immediate; n = 11 delayed) either had a negative explore or the foreign body was milked aborally into the colon at the time of surgery. Conclusion: Although outcomes were not associated with surgical timing, the unadjusted prevalence of gastrointestinal injury and, thus, the requirement for complex surgical procedures was higher in the delayed group. Clinical significance: Earlier surgical treatment of stabilized dogs with GIFBO may involve fewer complex procedures and accelerate recovery.